Case Report: Endoscopic lumbar interbody fusion using percutaneous unilateral biportal endoscopy and 3D printing for an andersson lesion in ankylosing spondylitis - Yuan, Xiaofeng; Tao, Rui; Zhu, Mengfei; Zhu, Jiajun (Frontiers in Surgery, 2025)
BackgroundAn Andersson lesion (AL) is a late-stage lesion of ankylosing spondylitis (AS) that can be misdiagnosed. If the patient has unbearable pain or symptoms indicative of neurological damage, then posterior fusion can be considered. Compared with open surgical procedures, combining Unilateral biportal endoscopy (UBE) and 3D-printing technologies for endoscopic lumbar interbody fusion (LIF) can offer the advantages of minimal trauma and the same effect. In this study, we first used UBE with endoscopic LIF for an AL between T12 and L1 in a 43-year-old male patient with good clinical outcomes.MethodsA 43-year-old man was admitted to our hospital due to recurrent back pain for 8 years. Based on imaging (computed tomography and radiography) findings, medical history, and clinical examination, we carried out an HLA-B27 blood test to confirm the diagnosis of AS with AL. Finally, we undertook fully endoscopic LIF with UBE based on a 3D-printing model. This patient's pre- and postoperative radiological and clinical results were presented.ResultsAccurate preoperative planning based on a 3D-printing model is strongly recommended for patients with an AL who have ambiguous anatomic landmarks. Applying endoscopic techniques and 3D-printing technologies to the surgical treatment of AL is completely feasible and has an edge in terms of tissue damage.ConclusionEndoscopic LIF with UBE based on a 3D-printing model showed a favorable clinical and radiological result and appears to be a safe and effective technique for an AL.